The Opinion Delivery Practices of the United States Supreme Court 1790-1945 - John P. Kelsh (Washington University Law Quarterly, 1999)
During Holmes’ tenure on the Court, 1902-32, opinions were presented unanimously 91% of the time. In the October 1951 Term, when the Court decided Youngstown, only 22% of the Court’s opinions were presented unanimously. The 1951 Term was not an aberration. The Vinson Court averaged a unanimity rate of only 27%. This statistical difference between the Holmes and Vinson eras is part of a larger history of changes in the way the Supreme Court delivers opinions. This Article tells the story of those changes, at least for the years 1790-1945. Proceeding era by era, I describe both external and internal change in the Court’s practices.
Keywords: Legal opinions; Judicial statistics; Law – History; United States. Supreme Court